2020
DOI: 10.3389/fped.2020.00121
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical Sub-setting of the First Episode of Severe Viral Respiratory Infection Based on Clinical Assessment and Underlying Airway Disease: A Pilot Study

Abstract: Introduction: Viral bronchiolitis is a term often used to group all infants with the first episode of severe viral respiratory infection. However, this term encompasses a collection of different clinical and biological processes. We hypothesized that the first episode of severe viral respiratory infection in infants can be subset into clinical phenotypes with distinct outcomes and underlying airway disease patterns.Methods: We included children (≤2 years old) hospitalized for the first time due to PCR-confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…The findings of the present study support and build on previous reports on the concept of phenotype-specific responses to different therapeutic options in viral bronchiolitis, in this case suggesting the cost-effectiveness of beta2AR agonist bronchodilators in infants of the phenotype of virus-induced wheezing and proasthmatic type 2 immune responses. 12 Our study results are in line with previous studies that have shown significant benefits in clinically important outcomes (and therefore presumptively also in unmeasured economic outcomes) in infants with viral bronchiolitis with some of the above-mentioned phenotypical features treated with medications used for pediatric asthma. [29][30][31] At this point, it is worth mentioning that Seumois et al 32 suggesting that the molecular program in circulating Th2 cells may influence BDR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study support and build on previous reports on the concept of phenotype-specific responses to different therapeutic options in viral bronchiolitis, in this case suggesting the cost-effectiveness of beta2AR agonist bronchodilators in infants of the phenotype of virus-induced wheezing and proasthmatic type 2 immune responses. 12 Our study results are in line with previous studies that have shown significant benefits in clinically important outcomes (and therefore presumptively also in unmeasured economic outcomes) in infants with viral bronchiolitis with some of the above-mentioned phenotypical features treated with medications used for pediatric asthma. [29][30][31] At this point, it is worth mentioning that Seumois et al 32 suggesting that the molecular program in circulating Th2 cells may influence BDR.…”
Section: Discussionsupporting
confidence: 91%
“…19 To reflect the proportion of infants with viral bronchitis that potentially could benefit from inhaled beta2AR agonist bronchodilators with the phenotypic-guided strategy, we calculated a weighted average of the proportion of patients with the above-mentioned proasthmatic or Th2-immune characteristics, as reported in the literature (RV isolation, [20][21][22][23] affection during nonpeak months or during non-RSV-predominant months, 20 family history of asthma in a first-degree relative, 20,21 age greater than 12 months, 21,24 history of atopic dermatitis, 21 and wheezing or subcostal retractions as the predominant clinical presentation among affected infants: "wheezing phenotype"). 12 All the probabilities of the phenotypic-guided strategy were adjusted based on the above-mentioned weighted average of the proportion of patients with proasthmatic type 2 immune responses.…”
Section: Model Structurementioning
confidence: 99%
“…Atypical CT imaging findings previously reported in adults with COVID‐19, such as bronchiectasis, air bronchogram, and pericardial effusion, were not identified in the pediatric COVID‐19 cases included (Table 1). The typical findings of pediatric viral respiratory infections (e.g., hyperinflation 48–50 ) were not reported in children with COVID‐19. An example of the typical radiological appearance of the most common abnormalities identified in pediatric COVID‐19 cases is shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The typical findings of pediatric viral respiratory infections (e.g., hyperinflation [48][49][50] were not reported in children with COVID-19.…”
Section: Characteristics Of Studies and Subjects Includedmentioning
confidence: 95%
“…Notably, this weighted scored system predicted the risk of recurrence of virus-induced LRTI illnesses, suggesting that bedside clinical parameters may help to identify the presence of recurrent virus-induced bronchial ASM hyperreactivity [72]. In addition, wheezing and family history of asthma showed the best predictive model for recurrence after viral LRTI hospitalisation [72], and young children with recurrent viral-induced wheezing had higher nasal airway levels of type 2 cytokines (IL-4/IL-13) [73].…”
Section: Bedside Parameters and Viral Bronchiolitis Respiratory Phenomentioning
confidence: 97%